Kwestie prawne związane z rozwiązaniem zrzeszeń wolnomularskich w II Rzeczypospolitej - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The author presents a brief overview of the importance of Freemasons in the political life of the Second Polish Republic. He then discusses the background and circumstances of the issuance by the President of Poland of a decree dissolving Masonic associations on 22 November 1938. Next he carries out a detailed legal analysis of the document, comparing it to the bill on fighting Freemasonry submitted in parliament by the MP Wacław Budzyński. He concludes with reflections on fighting political views, especially of opposition groups, by means of instruments under criminal law. That such instruments are used is evidence, according to the author, of the weakness of the political system in a given country
Keywords: presidential decree as a statutory instrument; Second Polish Republic; Minister of the Internal Affairs; President of the Second Polish Republic; Masonic associations